2021
DOI: 10.1002/aur.2538
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the right temporoparietal junction and ventromedial prefrontal cortex to theory of mind in autism: A randomized, sham‐controlled tDCS study

Abstract: Theory of Mind (ToM) is the ability to attribute subjective mental states to oneself and others and is significantly impaired in Autism Spectrum Disorder (ASD). A frontal-posterior network of regions including the ventromedial prefrontal cortex (vmPFC) and temporoparietal junction (TPJ) is involved in ToM. Previous studies show an underactivation of these regions in ASD.Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation method for causally investigating brain-behavior relationsh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 70 publications
(100 reference statements)
0
27
0
3
Order By: Relevance
“…Two recent studies also reported improving effects of frontocerebellar tDCS (i.e., anodal left dlPFC, cathodal right cerebellar tDCS) on behavioral symptoms (Toscano et al., 2019 ), and anodal stimulation over the primary motor cortex on motor skill training in children with ASD (Mahmoodifar & Sotoodeh, 2020 ). Of 11 included studies, only 1 study targeted right TPJ and vmPFC, two key regions in the theory of mind in ASD, and found that anodal vmPFC, but not r‐TPJ tDCS, significantly improved ToM in children with ASD (Salehinejad et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies also reported improving effects of frontocerebellar tDCS (i.e., anodal left dlPFC, cathodal right cerebellar tDCS) on behavioral symptoms (Toscano et al., 2019 ), and anodal stimulation over the primary motor cortex on motor skill training in children with ASD (Mahmoodifar & Sotoodeh, 2020 ). Of 11 included studies, only 1 study targeted right TPJ and vmPFC, two key regions in the theory of mind in ASD, and found that anodal vmPFC, but not r‐TPJ tDCS, significantly improved ToM in children with ASD (Salehinejad et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the last couple of years, however, tDCS has been increasingly used in children and adolescents (Rivera‐Urbina et al., 2017 ; Salehinejad et al., 2021 ; Vicario & Nitsche, 2013 , 2019 ). In child psychiatric disorders, tDCS has been mostly applied in neurodevelopmental disorders specifically attention‐deficit hyperactivity disorder (ADHD) (Salehinejad et al., 2021 , 2016 ; Westwood et al., 2021 ), autism spectrum disorder (ASD) (García‐Gonz ález et al., 2021 ; Osório & Brunoni, 2019 ), and developmental dyslexia (Salehinejad et al., 2021 ; Turker & Hartwigsen, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on data collected in non-clinical populations, it has been speculated that modulation of the rTPJ may have an impact on classic socially related patient symptomology. For example, Transcranial direct stimulation (tDCS) delivered to the right TPJ has been shown to improve behavioral issues associated with ASD [120]. Due to the relationship of the TPJ with mental and emotional state attribution, with similar processes associated with autism-relevant traits, tDCS to the TPJ has the ability to influence social-cognitive performance [121].…”
Section: Patients and Brain Stimulationmentioning
confidence: 99%
“…The Salehinejad study, in detail, examined the role of both the vMPFC (ventral Medial Prefrontal Cortex) and the rTPJ implying tDCS [120]. They found a greater clinical role for the vMPFC which indicates that the rTPJ is far from the only site responsible for these complex disorders.…”
Section: Patients and Brain Stimulationmentioning
confidence: 99%
“…An alternative technique is transcranial direct current stimulation (tDCS). Although tDCS has the significant drawback of offering much less focal stimulation than rTMS, it also has some advantages, such as having relatively long-lasting effects—about an hour after 12 min of stimulation [ 25 ]—a generally noticeable impact on performance and the possibility to use excitatory (anodal) or inhibitory (cathodal) stimulation [ 26 , 27 ]. In the social domain, the use of tDCS remains relatively limited, and to date, it has been mainly aimed at experimentally inducing changes in cognitive and social behavior in neurotypical individuals, to understand better the neural mechanisms of ToM.…”
Section: Introductionmentioning
confidence: 99%